MODEL REGENERASI DAN KADERISASI KEPEMIMPINAN DALAM ISLAM - Falah, Saiful; Hafidhuddin, Didin; Mujahidin, Endin; Bahruddin, E. (Faculty of training and education, Pamulang university, 2016)
This study aimed to find the model of regeneration in Islam as a solution to the above problems. Muhammad saw as the role model of Muslim leader has given us an example of how to grow leaders in a community. His model handed down to the companions and the previous followers. Therefore, his model in regenerating leaders can serve as a model for recent Muslim leaders to reproduce high quality leaders.The approach used in this study is library research. The research process begins with a search-related book titles, specify the primary sources about the history of Islam, including the life of The prophet, the chalips and muslim leaders. From those sourcesfoundedthe prohet and the chalips? thought about regeneration. Then the analysis is done and conclusions are drawn. The study also called qualitative research, therefore qualitative methods applied to use descriptive writing techniques.This research concludes that, the model of regeneration served by the prophet and the chalips is important for the recent Muslim leaders to reproduce high quality Muslim leaders. The model includes; regeneration in Islam based on Syura, akhlak as the basic value of regeneration, the program of regeneration including appreciation, direction, assignment and modeling, the modeling or giving good example is the main program. Keywords: Islam, Kaderisasi, Kepemimpinan, Regenerasi